2018
DOI: 10.1039/c7gc02577g
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable succinylation of cellulose in a CO2-based switchable solvent and subsequent Passerini 3-CR and Ugi 4-CR modification

Abstract: An effective and sustainable succinylation of cellulose is described. The thus introduced carboxylic acids groups allowed a straightforward modification of cellulose via multicomponent reactions in a unprecedented manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 53 publications
0
39
0
1
Order By: Relevance
“…To suppress the degradation, a tertiary base, such as pyridine and triethylamine, is recommended as the solvent medium as well as the acylation catalyst for the esterification with acid anhydrides (Heinze et al 2006). Söyler et al (2018) reported a rapid and efficient dissolution and activation of cellulose for the subsequent esterification with succinic anhydride in a CO 2 based switchable solvent for only 30 min at room temperature (Fig. 2a).…”
Section: Fundamental Aspectsmentioning
confidence: 99%
“…To suppress the degradation, a tertiary base, such as pyridine and triethylamine, is recommended as the solvent medium as well as the acylation catalyst for the esterification with acid anhydrides (Heinze et al 2006). Söyler et al (2018) reported a rapid and efficient dissolution and activation of cellulose for the subsequent esterification with succinic anhydride in a CO 2 based switchable solvent for only 30 min at room temperature (Fig. 2a).…”
Section: Fundamental Aspectsmentioning
confidence: 99%
“…reported that Passerini and Ugi reactions could be applied for the modification of succinylated cellulose in dimethyl sulfoxide (DMSO). [ 20 ] Kabachnik−Fields reaction was used by Hamada et al. on cellulose fabric surface modified by methacrylated vanillin.…”
Section: Figurementioning
confidence: 99%
“…49,50 This is in keeping with prior reports of efficient multicomponent reactions in ionic liquids and deep eutectic salts. [51][52][53][54][55] The model coupling described above in each of, ethylammonium nitrate (EAN), propylammonium nitrate (PAN) and ethanol ammonium nitrate (ETAN) with microwave irradiation was evaluated aer 5 min irradiation at 50 C, 100 C and 120 C ( Table 2). Pleasingly aer 5 min irradiation at 100 C, with EAN, a 58% recovery of pure 12 was achieved, increasing to 60% at 120 C with a similar outcome noted with PAN.…”
Section: Rsc Advances Papermentioning
confidence: 99%